Perceived gender discrimination, belief in a just world, self-esteem, and depression in Korean working women: A moderated mediation model - Kim, Eunha; Park, Hansol (Women's Studies International Forum, 2018)
Past research has found that perceived gender discrimination is related to women's poor mental health outcomes. However, despite the high prevalence of gender discrimination in South Korea, this relationship, and the mechanism that explains such a relationship remains understudied. The current study investigated married Korean working women's perceptions of gender discrimination, self-esteem, belief in a just world, and depression by testing a moderated mediation model. The results suggest that perceived gender discrimination was negatively related to self-esteem, but only at high levels of belief in a just world. In addition, we found support for a moderated mediation effect in which self-esteem mediated the relationship between perceived gender discrimination and depression, but only at high levels of belief in a just world. These findings contribute to the literature by highlighting the relevance of a belief in a just world to an understanding of women's self-esteem and depression in the context of gender discrimination.
Keywords: Belief in a just world; Depression; Korea; Perceived gender discrimination; Self-esteem